East Asian Herbal Medicine to Reduce Primary Pain and Adverse Events in Cancer Patients : A Systematic Review and Meta-Analysis With Association Rule Mining to Identify Core Herb Combination - Jo, Hee-Geun; Seo, Jihye; Choi, Seulki; Lee, Donghun (Frontiers in Pharmacology, 2022)
Objective: Cancer pain is an important factor in cancer management that affects a patient's quality of life and survival-related outcomes. The aim of this review was to systematically evaluate the efficacy and safety of oral administration of East Asian herbal medicine (EAHM) for primary cancer pain, and to explore core herb patterns based on collected data. Methods: A comprehensive literature search was conducted in 11 electronic databases for randomized controlled trials from their inception until August 19, 2021. When heterogeneity in studies was detected, the cause was identified through meta regression and subgroup analysis. Methodological quality was independently assessed using the revised tool for risk of bias in randomized trials. Results: A total of 38 trials with 3434 cancer pain patients met the selection criteria. Meta-analysis favored EAHM combined conventional medicine on response rate, continuous pain intensity, duration of pain relief, performance status, and opioid usage. No significant difference between EAHM and conventional medicine on response rate and other outcome. Patients treated with EAHM had significantly reduced Adverse event incidence rates. In addition, based on ingredients of herb data in this meta-analysis, four combinations of herb pairs, which were frequently used together for cancer pain, were derived. Conclusion: EAHM monotherapy can lead to decrease adverse events associated with pain management in cancer patients. Additionally, EAHM combined conventional medicine therapy may be beneficial for cancer pain patients in increasing response rate, relieving pain intensity, and improving pain-related performance status, and regulating opioid usage. However, the efficacy and safety of EAHM monotherapy are difficult to draw conclusions due to lack of methodological quality and quantity of studies. More well-designed, multicenter, double-blind, and placebo-controlled randomized clinical trials are needed in future studies. In terms of the core herb combination patterns derived from the present review, four combinations of herb pairs that might be promising for cancer pain because they have been often distinctly used for cancer patients in East Asia. Thus, they are considered to be worth a follow-up study to elucidate their actions and effects.